Evaluation of polymers for upper limb orthosis through computer simulation (Research, Society and Development, 2022)
Material selection is one of the most relevant and challenging steps in engineering projects. In this study, we focused on selecting polymers with low density and stiffness for upper limb orthoses that help in the recovery of patients who have undergone cerebrovascular accident (CVA). CES EduPack 2011 software was used to compare the density and Young's modulus of different polymers. The merit index aided in the classification of these materials, which were applied to 3D orthosis models for computer simulations in FreeCAD 0.19.4 software. Using the simulation data, a decision matrix was developed using the Pahl & Beitz method to classify polymers according to the weighted property index. The decision matrix using the simulated and merit index data indicated polyethylene terephthalate (PET) and polylactic acid (PLA) as the best polymers for upper limb orthoses. The weighted property index values were 127.34 and 123.19, respectively. It is noteworthy that polyethylene terephthalate glycol (PETG - adaptation of PET) is an alternative to 3D printing filaments, and PLA is one of the main filaments.